2021
DOI: 10.4314/mmj.v33i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an educational programme on critical care nurses’ competence at two tertiary hospitals in Malawi

Abstract: BackgroundCritical care specialty deals with the complex needs of critically ill patients. Nurses who provide critical care are expected to possess the appropriate knowledge and skills required for the care of critically ill patients. The aim of this study was to assess the effect of an educational programme on the competence of critical care nurses at two tertiary hospitals in Lilongwe and Blantyre, Malawi.MethodsA quantitative pre- and post-test design was applied. The training programme was delivered to nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…The sample is based on similar studies that have implemented interventions for health professionals. For example, a study by Gundo et al 41 used G-Power software 42 to calculate the sample size based on a conservative effect size of d=0.5, a power of 80% and an alpha=0.05. The calculated sample size was 34, but 41 participants were invited to participate in training to allow for a dropout rate of at most 20%.…”
Section: Phasementioning
confidence: 99%
“…The sample is based on similar studies that have implemented interventions for health professionals. For example, a study by Gundo et al 41 used G-Power software 42 to calculate the sample size based on a conservative effect size of d=0.5, a power of 80% and an alpha=0.05. The calculated sample size was 34, but 41 participants were invited to participate in training to allow for a dropout rate of at most 20%.…”
Section: Phasementioning
confidence: 99%
“…Aplikasi teknologi yang mudah digunakan menjadi sangat penting. (Mukhlisah, 2019); (Anando & Gundo, 2021); (Simbolon et al, 2022); (Rohmanurmeta & Dewi, 2018).…”
Section: Pembelajaranunclassified
“…[14] In addition, studies have shown that education can improve nurses' knowledge and practices in the management of critically ill patients, leading to better patient outcomes. [15][16][17] Higher ratios of nurses with specialized critical care training have also been linked to better patient outcomes. [18] Maintaining adequate staffing levels is essential when developing a workforce emergency plan.…”
Section: Introductionmentioning
confidence: 99%